Effect of "PMSG" of different origins on superovulation in mice - Jaume, Carlos Miguel; Campos, Ana Lucia (Pesquisa Agropecuaria Brasileira, 1992)
Female mice were superovulated with PMSG from different origins: local (PMSG-N), from France (PMSG-F) and from Canada (PMSG-C). Two response curves were studied using 5, 10, and 20 I.U. of PMSG-N, one collecting embryos at the two-cell stage and the other collecting morula. For both response curves there was an extra treatment, using the lowest dose, in the case of collection at the two cell stage, with PMSG-F and in the case of morula with PMSG-C. There was no statistically significant difference (P > 0,05) between doses of PMSG-N in number of structures or in number of viable embryos collected, either at the two-cell, or the morula stage of development. In animals injected with 5 I.U. of PMSG, there was a statistically significant (P < 0,5) difference in the number of viable embryos collected among animals injected with either PMSG-F or PMSG-C and those injected with PMSG-N, and in the number of structures collected among the animals injected with PMSG-N and PMSG-C. The number of viable embryos collected from animals injected with 5 I.U. of PMSG-F or PMSG-C, was double that obtained injecting PMSG-N.